EVALUTION OF BIOCONTROL AGENT BACILLUS SUBTILIS B5 FOR CONTROL OF PHYTOPHTHORA INFESTANS ON POTATO LEAVES - Sunaina, V; Ajay, S (Potato Journal, 2013)
Foliar infection during five days period of incubation at 18Â°C and humidity above 90% revealed no appearance of Phytophthora infestans lesions till 96 h of incubation where five leaflets in each set were abaxially sprayed with 106 cfu/ml suspension of biocontrol agent Bacillus subtilis B5 and 0.2% concentration of a mancozeb + metalaxyl formulation. The leaflets in control set exhibited average infection severity index of 1.8 and 3.8 after 72 and 96 h of incubation, respectively. After 120 h of incubation, the average infection severity index of 0.6 and 0.2 was recorded in bca B5 and fungicide formulation sprayed leaves compared to control where infection severity index of 4.0 to 5.0 was recorded in foliar tissues of all the five leaflets of a set resulting in an average infection severity index of 4.8.